Group Genius : The creative power of collaboration - Sawyer, R. Keith (Robert Keith) (2017)
Creativity has long been thought of as an individual gift, best pursued alone; schools, organisations, and whole industries are built on this idea. But what if this most common belief about how creativity works is wrong? Pychologist Keith Sawyer tears down some of the most popular myths about creativity and erects new principles in their place.
Previous edition: 2007.
Includes bibliographical references and index.
Keywords: Group problem solving; Creative thinking; Business and Management